Efficacy of Plyometric Training on the Agility in Police Cadets - Dushyant Bawiskar1 , Pratik Phansopkar2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Plyometric training is a hybrid between strength and endurance training. This allows musclesexert maximum force in short intervals of time, with the goal of increasing power (speed-strength) whichensures better agility in police cadets. Agility has been defined by the capacity to retain or determine thelocation of body by shifting its direction rapidly in a sequence of movements. Agility, speed and explosivepower are qualifying components of physical fitness and desirable athletic performance, and play a key rolein most sports. Agility can enhance the coordination and regulation of locations of the body throughoutmovement.Objective: To study the efficacy of the 6-weeks and 12-weeks Plyometric training on the agility in policecadets.Method: 40 Cadets aged above 18 years were grouped into two. A group continued their regular activitieswhile rest underwent 2 sessions of plyometric training every week for 6 weeks, along with their dailyactivities. Analysis was then carried out with assessment of T-test Agility test, Illinois Agility Test, EdgrenSide Step Test. Study duration is 6 months and intervention duration is 12-weeks, hence participants will beenrolled during first 3-months of study so 12 week intervention will be completed successfully. Assessmentwill be done on 1st day of visit then at the end of 6th week and again at the end of 12th week. Participantswould have to perform 2 session of Plyometric Training per week in other group.Result: Data will be analyzed using paired T-test.Conclusion: Will be published after the results are analyzed.